¿Cómo se lee un cuento etnográfico? - Mancha, Luis (Revista de Antropología Social, 2008)
F. S. P. suggests two possibilities in “The devil of the fiction. An ethnographic short story”. Concerning the formal side, a new way of telling is suggested; while on the content side, the author draws the line between Anthropology and Literature, fiction and reality. Taking this as a starting point, this article analyzes the two levels contained in this “artistory” -as the author himself calls it-. On the one hand, the idea of ethnographic short story implies the creation of a hybrid genre, between essay and fiction; it could even be considered an oxymoron. However, this proposal affects the reading process because the official statute of the text and horizon of reading are substantially changed, and as a result the pact between author and readers must also be altered. On the other hand, this article analyzes the terms, suggested by F. S. P. of the discussion between Anthropology and Literature. To do this, this discourse must be placed in the social conditions of its production. The key to concepts such as literature, fiction or writer that are used by the main characters of this story, are to be found in the position of the author in the anthropological and literary fields. Thanks to this sociological reading of textual discourse, interesting conclusions on the terms of the discussion between Anthropology and Literature can be taken.